The Influence of Perceived Ease of Use, Perceived Risk and Consumer Trust towards Merchant Intention in using QRIS as a Digital Payment Method - Maria Andriani Halimah Pontoh; Frederik G. Worang; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2022)
The purpose of this research is to analyze the influence of Perceived Ease of Use, Perceived Risk and Consumer Trust towards Merchant Intention in using Quick Response Code Indonesian Standard (QRIS) simultaneously or partially. This research method uses questionnaire data collection techniques with the respondent data of 100 people. The result showed that Perceived Ease of Use has significant effect on Merchant Intention in using QRIS as a digital payment method, while Perceived Risk and Consumer Trust has no significant effect on Merchant Intention in using QRIS as a digital payment method. From these results, it is recommended for merchants who have not switched to non-cash transactions, it is hoped that they can use QRIS as a digital payment method, considering that QRIS has low risk, is easy to use and can save time quickly and efficiently. Also, it is recommended for further researchers to able to expand this research.